Plastic and fracture behaviour of nanocrystalline binary Al alloys with grain boundary segregation - Dmitriev, S. V. (2019)
The paper studies the stress-strain and fracture behaviour of nanocrystalline (NC) pure Al and NC binary Al-X alloys (X can be Fe, Co, Ti, Mg or Pb) with grain boundary (GB) segregation during their tensile deformation at room temperature via molecular dynamics simulation. The computational cell used for the modeling contains nano-sized grains of Al majority of which has the high-angle type GBs. The binary alloys were obtained through the substitution of Al atoms in GBs by atoms of the alloying elements. Stress-strain curves of the considered materials were calculated, and their microstructure evolution was analyzed. It was found that GB segregations can significantly alter the deformation behaviour of NC Al. The NC pure Al and two alloys, Al with Fe and Al with Mg, undergo the intergranular fracture which is noticeable already at ~ 8 % strain, while the other alloys do not demonstrate any failure process up to 40 % deformation. The main crack growth mechanism is the formation of nano-voids at GBs and triple junctions followed by their coalescence at higher applied stresses. The obtained results demonstrate that GB segregation of Co can have a positive effect on both plasticity and strength of NC Al, and Ti atoms in GBs can result in its improved ductility.